K KUALITAS FISIK TELUR BURUNG PUYUH YANG DIBERI PAKAN DENGAN PENAMBAHAN TEPUNG BEKICOT - Muh Akramullah; R. R. Depawole; N. A. D. Tiya (Jurnal Sain Peternakan Indonesia, 2023)
This study aims to see the physical quality of quail eggs (Coturenix-coturnix japonica) fed with snail flour (Achatina fulica). The quail used as many as 72 tails, averaging 42 days of age. The maintenance of quail in this study was carried out intensively (caged). During the research, quail was given feed treatment at 07:00 WITA and 16:00 WITA, while drinking water was given in a libitum. The parameters observed in this study were egg weight, Haugh unit, yolk weight, yolk index, yolk color, albumen weight, albumen index, shell weight, and thickness of the shells. This research uses a complete random (CRD) design with three treatments and four replications. The research treatment is divided into three experimental treatments as follows: P0 (feed + snail flour 0%), P1 (feed + snail flour 5%), and P2 (feed + snail flour 10%). Giving snail flour into the feed significantly has a significant effect on the weight of eggs, yolk weight, yolk color, albumen index, shell weight, and thickness of quail shells (P <0.05), while Haugh units (P> 0.05). The results of this study can be concluded that adding snail flour up to 5-10% can produce a higher physical quality of the eggs compared to the treatment without the addition of snail flour into the feed.